THE COMPARISON BETWEEN PRODUCT CLASS KNOWLEDGE, PERCEIVED RISK, AND ATTITUDE TOWARDS GENERIC DRUGS - Anisa Anisa; Sugiyanto Sugiyanto; M. Rifqi Rokhman (Faculty of Pharmacy, Universitas Gadjah Mada)
People often consider that generic drugs are inferior drugs. Knowledge holds big roles in consumer decision making process, including in purchasing generic drugs. Students of health sciences got different understanding compared to students of non health sciences about to knowledge of generic drugs. Therefore, this study aimed to get better understanding and compare product class knowledge, perceived risk, and attitude towards generic drugs in students of health sciences versus students of non health sciences. The population of this non experimental study was Gadjah Mada University students. Sampling technique was using purposive sampling. Samples were UGM students of health sciences and students of non health sciences who met inclusion criteria. Data were collected using questionnaires and analyzed using path analysis and Mann-whitney. Results of this study showed that there was significant negative influence between objective knowledge and perceived risk (standardized coefficient beta value = -0.368), subjective knowledge and perceived risk (standardized coefficient beta value = -0.485), prior experience and perceived risk (standardized coefficient beta value = -0.485), and perceived risk and attitude toward generic drugs (standardized coefficient beta value = -0.489). There were difference between health students and non health students on their product class knowledge, perceived risk and attitude towards generic drugs, which health students got higher product class knowledge and attitude towards generic drugs, while non health students got higher perceived risk compared to health students. Keywords: product class knowledge, perceived risk, attitude towards generic drugs, generic drugs.